2023
DOI: 10.1088/2057-1976/acb550
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of deep learning based implanted fiducial markers tracking in pancreatic cancer patients

Abstract: Real-time target position verification during pancreas stereotactic body radiation therapy (SBRT) is important for the detection of unplanned tumour motions. Fast and accurate fiducial marker segmentation is a requirement of real-time marker-based verification. Deep learning (DL) segmentation techniques are ideal because they don’t require additional learning imaging or prior marker information (e.g., shape, orientation). In this study, we evaluated three DL frameworks for marker tracking applied to pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Some studies ( 52 , 54 , 57 , 63 ) have used real 2D kV X-ray images to train their models, thus mitigating the potential effects resulting from discrepancies between the simulated images and real images; however, some limitations persisted. It should be noted that the tracking target of reference ( 52 ) is the fiducial marker, and the question of whether it is efficient for marker-less target tracking requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies ( 52 , 54 , 57 , 63 ) have used real 2D kV X-ray images to train their models, thus mitigating the potential effects resulting from discrepancies between the simulated images and real images; however, some limitations persisted. It should be noted that the tracking target of reference ( 52 ) is the fiducial marker, and the question of whether it is efficient for marker-less target tracking requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…And Kim et al ( 54 ) localized the lumbar vertebrae only and reported a mean center position error of 5.07±2.17 mm; however, this slightly large error could limit the application of the model in the clinic. Hirai et al ( 57 ) and Ahmed et al ( 63 ) also used real 2D kV images, but the input of their models was the sub-images cropped from the real images. The use of sub-images as input may limit the ability of the deep-learning model to extract global features and possibly decrease the tracking accuracy, especially when tumor and organ positions inter-fractionally change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation